2013
DOI: 10.1002/jbm.a.34709
|View full text |Cite
|
Sign up to set email alerts
|

Performance of conical abutment (Morse Taper) connection implants: A systematic review

Abstract: In this systematic review, we aimed to compare conical versus nonconical implant-abutment connection systems in terms of their in vitro and in vivo performances. An electronic search was performed using PubMed, Embase, and Medline databases with the logical operators: "dental implant" AND "dental abutment" AND ("conical" OR "taper" OR "cone"). Names of the most common conical implant-abutment connection systems were used as additional key words to detect further data. The search was limited to articles publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
187
1
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(212 citation statements)
references
References 65 publications
10
187
1
14
Order By: Relevance
“…Supporting the present results, Schmitt et al (14) suggested that no cold welding may be obtained in nontapered systems and the tapered interface provides a more precise fit. However, Jansen et al (2) found no difference between 13 combinations of implant/abutment systems, including tapered, non-tapered and tapered indexed, where all combinations showed bacterial leakage in vitro and most samples showed contamination on the first day.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Supporting the present results, Schmitt et al (14) suggested that no cold welding may be obtained in nontapered systems and the tapered interface provides a more precise fit. However, Jansen et al (2) found no difference between 13 combinations of implant/abutment systems, including tapered, non-tapered and tapered indexed, where all combinations showed bacterial leakage in vitro and most samples showed contamination on the first day.…”
Section: Discussionsupporting
confidence: 87%
“…Schmitt and colleagues (14) demonstrated that the tapered connections were superior regarding their sealing capacity in vitro, more resistant to abutment movement as well as to widening of the abutment/implant interface under load. They also presented greater resistance to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present investigation agree with those reported by Jansen et al, 30 in which the three conical abutment interfaces evaluated showed evidence of leakage. In a systematic review, Schmitt et al 31 reported that although no connection is 100% effective, conical connections seem to provide a superior bacterial seal. In contrast, however, Dibart et al 9 found no bacterial penetration of the interface from within the implant or from the surrounding bacterial solution, when evaluating the seal of the 1.5° locking taper design at the interface.…”
Section: Discussionmentioning
confidence: 99%
“…These design features could lead to improvements compared to nonconical connection systems. 26 Hence, using the appropriate torque in conical internal connection implants and decreasing the gap immediately after the insertion of the abutment can reduce the possibility of any bacterial contamination that occurs simultaneously with the loading of the implant at the time of prosthesis placement, because these factors, together, depending on the patient's sensitivity threshold, could cause trauma to peri-implant tissues.…”
Section: Discussionmentioning
confidence: 99%